Faculty Roles: Unending, Unbundling, or Unraveling? - JACQUELINE KRESS (Academic Chairpersons Conference Proceedings, 2020)
More new adjuncts than new tenure-track faculty? Enrollment and budgets contribute, but the “adjunctification” trend is more complex. The steady unbundling of faculty roles is an important but less recognized contributor. This session overviews the unbundling phenomenon and positions faculty to make informed decisions at their home campuses.
Keywords: Faculty roles; unbundling faculty roles; technology and college curriculum; college staffing trends